Magnetically reshapable 3D multi-electrode arrays of liquid metals for electrophysiological analysis of brain organoids - Enji Kim; Eunseon Jeong; Yeon-Mi Hong; Inhea Jeong; Junghoon Kim; Yong Won Kwon; Young-Geun Park; Jiin Lee; Suah Choi; Ju-Young Kim; Jae-Hyun Lee; Seung-Woo Cho; et al. (Nature Communications)
Abstract To comprehend the volumetric neural connectivity of a brain organoid, it is crucial to monitor the spatiotemporal electrophysiological signals within the organoid, known as intra-organoid signals. However, previous methods risked damaging the three-dimensional (3D) cytoarchitecture of organoids, either through sectioning or inserting rigid needle-like electrodes. Also, the limited numbers of electrodes in fixed positions with non-adjustable electrode shapes were insufficient for examining the complex neural activity throughout the organoid. Herein, we present a magnetically reshapable 3D multi-electrode array (MEA) using direct printing of liquid metals for electrophysiological analysis of brain organoids. The adaptable distribution and the softness of these printed electrodes facilitate the spatiotemporal recording of intra-organoid signals. Furthermore, the unique capability to reshape these soft electrodes within the organoid using magnetic fields allows a single electrode in the MEA to record from multiple points, effectively increasing the recording site density without the need for additional electrodes.